Geometrical and electrostatic densities in a highly sparse as-electrospun polystyrene microfiber mat - Yuya Ishii (Materials Letters: X, 2023)
Electromechanically active nano/microfibers are promising components of sensors and actuators; however, piezoelectric polymers are normally expensive. To address this issue, this study examined the geometrical and electrostatic densities of an inexpensive highly sparse as-electrospun atactic polystyrene microfiber mat. The densities of porous individual fibers and the highly sparse fiber mat were experimentally determined to be 0.88 and 0.051 g cm−3, respectively, with corresponding material filling ratios of 80 % and 4.7 %, respectively. A high theoretical surface charge density of approximately 1.4 × 10−3 C m−2 was determined for the fiber mat after excluding air spaces in both individual fibers and the mat. These findings provide a pathway to outstanding electrets that are ultra-lightweight and have high charge densities.